Odpowiedzi

2010-01-05T22:53:53+01:00
A )
2 + x /2 = 1 - x /3 /*
3(2+x)=2(1-x)
6+3x=2-2x
5x=-4 /:5
x=4/5

b )
- x + 3 /5 - 1 = 3 - 5x /2 /*8
2(-x+3)=4(3-5x)
-2x+6=12-20x
18x=6 /:18
x=1/3

niewiem jak odczytać przyklad c
11 2 11
Najlepsza Odpowiedź!
2010-01-05T22:55:36+01:00
A ) 2 + x /2 = 1 - x /3
2-1=-x/3-x/2 /*6
12-6=-2x-3x
6=-5x
x=-5/6

b ) - x + 3 /5 - 1 = 3 - 5x /2 /*10
-10x+6-10=30-25x
-10x -4=30-25x
-10x+25x=30+4
15x=34
x=34/15
x=2 4/15 (to jest dwa i cztery piętnaste)


c ) - 2x-1 /9 + 4x-5 /15 = x-5
2x-1/9-5/15=x-5
2x-x-1/9 - 1/3=-5
x-1/9 - 3/9 =-5
x-4/9=-5
x=-5+4/9
x= 5 4/9 (pięć i cztery dziewiąte)



14 2 14